2019
DOI: 10.1007/s11067-019-09482-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions in Spatial Networks: a Comparative Study of Major Shocks Affecting Ports and Shipping Patterns

Abstract: In this research, the effect of local exogenous shocks on seaports and maritime networks is assessed throughout three case-studies. The Hanshin-Awaji earthquake, the 9/11 World Trade Center attack and hurricane Katrina triggered a shock on Kobe, New York and New Orleans respectively and led to temporary port failures. A global database on vessel movements is computed to gauge the intensity, duration and scope of these shocks with descriptive statistics. Port-centered analyses of the disrupted ports and their g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…Wu et al (2019) found that global shipping times would increase by 25% without Suez, especially between the main economic poles of the Northern hemisphere, while more than 50% East Asian and European container shipping depend on the Malacca Strait and the Suez Canal. Rousset and Ducruet (2020) demonstrated strong affinities between New York, Kobe, and New Orleans, and the significant correlation between distance to shock epicenter and neighbor ports' ulterior traffic change. They also compared the connectivity of the three ego-networks before and after the shocks, characterized by an increasing density.…”
Section: Hubs and Vulnerability At Different Scalesmentioning
confidence: 99%
“…Wu et al (2019) found that global shipping times would increase by 25% without Suez, especially between the main economic poles of the Northern hemisphere, while more than 50% East Asian and European container shipping depend on the Malacca Strait and the Suez Canal. Rousset and Ducruet (2020) demonstrated strong affinities between New York, Kobe, and New Orleans, and the significant correlation between distance to shock epicenter and neighbor ports' ulterior traffic change. They also compared the connectivity of the three ego-networks before and after the shocks, characterized by an increasing density.…”
Section: Hubs and Vulnerability At Different Scalesmentioning
confidence: 99%
“…In that respect, our work is more focused on the perspective of shippers and on how the characteristics of containerized services at ports have been affected by a global shock. Furthermore, as suggested by Rousset and Ducruet (2020) , the maritime network and its response to shocks depend on many different actors and the knowledge regarding how their individual decisions are made is limited. It is thus interesting to complement network approaches with empirical ones.…”
Section: Introductionmentioning
confidence: 99%
“…The role of geography has been recognized by Rousset and Ducruet (2020) , who studied the effects of Hanshin's earthquake, together with the 9/11 World Trade Center attack and hurricane Katerina, on a network perspective. They measured how shocks strongly localized on ports simultaneously affected other ports in the network.…”
Section: Introductionmentioning
confidence: 99%
“…The costs of all those actions and their consequences can be estimated 20 24 , together with aggregate measures of resilience and rapidity of recovery. Only few works 3 study empirical dynamics of existing disruptions in their effects to transport performance, or choices of travelers 20 22 , 25 27 , possibly due to unavailability of data, or complexity of interacting effects. With the recent outbreak of COVID-19 and restricted mobility, a large interest in studies on demand or supply changes developed 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The links themselves, i.e. the oceanic course of a vessel, are operated point-to-point, and rarely completely disrupted 27 . The availability of vehicles and crew is crucial in operating the network.…”
Section: Introductionmentioning
confidence: 99%